Comparative electromyography analysis of the upper extremity between inexperienced and elite water polo players during an overhead shot - Yaghoubi, M.; Esfehani, M. M.; Hosseini, H. A.; Alikhajeh, Y.; Shultz, S. P. (Journal of Applied Biomechanics, 2015)
The aim of this study was to compare muscle activity patterns between inexperienced and experienced water polo players while taking an overhead shot. The study was carried out with a group of 12 water polo players and an inexperienced group of 10 healthy participants. Signals were recorded by surface electromyography from six different muscles. The average and standard deviation of the normalized electrical activity, time to peak, time broadness, and muscle sequencing during the overhead shot were determined for each muscle in both groups and compared with each other. In water polo players, the normalized electrical activities of triceps brachii, pectoralis major, and wrist flexors were greater than other muscles, while in the inexperienced group the triceps brachii specifically played an important role. There was minimal activation of the middle deltoid and biceps brachii in water polo players. Increased times to peak and time broadness of muscles were found in the inexperienced group compared to experienced water polo players; this difference may be explained by different neuromuscular proprioception. Only experienced water polo players activated the observed muscles in a specific sequence, from proximal to distal. Therefore, coaches should emphasize smooth and quick transitions from proximal to distal segments, with less importance placed on individual muscle strengthening.